3D CFD Simulations: Effect of Operation Parameters on the Deposition of Photocatalytic TiO2 Nanoparticles by MOCVD. Issue 4 (7th January 2015) - Othman, Siti Hajar; Abdul Rashid, Suraya; Mohd. Ghazi, Tinia Idaty; Abdullah, Norhafizah
Abstract : A 3‐dimensional (3D) computational fluid dynamics (CFD) simulation study on the effect of temperature and carrier‐gas flow rate on the deposition of photocatalytic titanium dioxide (TiO2 ) nanoparticles by metal‐organic (MO)CVD is presented. The model predicts the temperature, velocity, mass fraction of reactants and products, kinetic rate of reaction, and surface deposition rate profiles. Increasing temperature and reducing carrier gas flow rate increases the deposition rate and hence the amount of nanoparticles produced. Unlike carrier‐gas flow rate, temperature is significant in determining the rate of surface deposition. Simulation results are validated by experiments whenever possible due to limited data. Decent agreement between experiment and simulation supports the reliability of the simulation. Abstract : A 3D computational fluid dynamics (CFD) simulation investigation on the effect of imperative operation parameters (deposition temperature between 500 and 900 °C and carrier‐gas flow rate between 0.2 and 0.6 slm) was performed on the deposition of photocatalytic TiO2 nanoparticles by metal‐organic (MO)CVD. Surface deposition rate, and hence the amount of nanoparticles produced, increased with the increase in deposition temperature and decrease in carrier‐gas flow rate.